2020
DOI: 10.1085/jgp.201811998
|View full text |Cite
|
Sign up to set email alerts
|

Structural mechanisms of transient receptor potential ion channels

Abstract: Transient receptor potential (TRP) ion channels are evolutionarily ancient sensory proteins that detect and integrate a wide range of physical and chemical stimuli. TRP channels are fundamental for numerous biological processes and are therefore associated with a multitude of inherited and acquired human disorders. In contrast to many other major ion channel families, high-resolution structures of TRP channels were not available before 2013. Remarkably, however, the subsequent “resolution revolution” in cryo-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 246 publications
(377 reference statements)
0
82
0
Order By: Relevance
“…The recently obtained high-resolution structures for several of these channels have shown that they are formed by four subunits (tetramer) [5,6], Figure 1, where each monomer is a six-pass transmembrane protein (S1-S6), with the N-and C-terminus intracellularly localized [6]subunits contain a re-entrant loop located between S5-S6, forming the pore or ion conduction pathway. Some of these channels contain ankyrin repeat domains (ARDs) in the N-terminus and a TRP-domain (a highly conserved 25-amino-acid α-helix structure parallel to the inner plasma membrane) at the C-terminus [5,6], Figure 2. The recently obtained high-resolution structures for several of these channels have shown that they are formed by four subunits (tetramer) [5,6], Figure 1, where each monomer is a six-pass transmembrane protein (S1-S6), with the N-and C-terminus intracellularly localized [6].…”
Section: Trp Channelsmentioning
confidence: 99%
See 3 more Smart Citations
“…The recently obtained high-resolution structures for several of these channels have shown that they are formed by four subunits (tetramer) [5,6], Figure 1, where each monomer is a six-pass transmembrane protein (S1-S6), with the N-and C-terminus intracellularly localized [6]subunits contain a re-entrant loop located between S5-S6, forming the pore or ion conduction pathway. Some of these channels contain ankyrin repeat domains (ARDs) in the N-terminus and a TRP-domain (a highly conserved 25-amino-acid α-helix structure parallel to the inner plasma membrane) at the C-terminus [5,6], Figure 2. The recently obtained high-resolution structures for several of these channels have shown that they are formed by four subunits (tetramer) [5,6], Figure 1, where each monomer is a six-pass transmembrane protein (S1-S6), with the N-and C-terminus intracellularly localized [6].…”
Section: Trp Channelsmentioning
confidence: 99%
“…Some of these channels contain ankyrin repeat domains (ARDs) in the N-terminus and a TRP-domain (a highly conserved 25-amino-acid α-helix structure parallel to the inner plasma membrane) at the C-terminus [5,6], Figure 2. The recently obtained high-resolution structures for several of these channels have shown that they are formed by four subunits (tetramer) [5,6], Figure 1, where each monomer is a six-pass transmembrane protein (S1-S6), with the N-and C-terminus intracellularly localized [6]. The subunits contain a re-entrant loop located between S5-S6, forming the pore or ion conduction pathway.…”
Section: Trp Channelsmentioning
confidence: 99%
See 2 more Smart Citations
“…TRPV channels are activated by chemical ligands, such as capsaicin or cannabinoids, but also by noxious heat (>43 • C), low pH (<6) (Caterina et al, 1997;Tominaga et al, 1998) and voltage changes inducing depolarization (Cao, 2020). TRPVs are also activated by lipid signaling (Cortright and Szallasi, 2004;Jung et al, 2004), and eicosanoids, signaling molecules produced by the enzymatic or non-enzymatic oxidation of arachidonic acid or other similar polyunsaturated fatty acids (Hwang et al, 2000).…”
Section: Activation Mechanisms Of Trpsmentioning
confidence: 99%